Perbandingan asuransi kesehatan di Indonesia dan Thailand - Azzahro, Salsa Billa Dwi (Maliki Interdisciplinary Journal, 2026)
Health insurance plays a crucial role in ensuring equitable and affordable access to healthcare services. In Thailand, the Universal Coverage Scheme (UCS), launched in 2002, has achieved nearly 99% population coverage by 2025, with full financing from general taxes. UCS provides comprehensive healthcare services without additional costs for citizens, including vulnerable groups such as the poor and informal workers. In Indonesia, the National Health Insurance (JKN), introduced in 2014, reached 95.75% coverage by 2023, but access to healthcare services remains uneven between urban and rural areas. This article compares the two health insurance systems, focusing on population coverage, financing mechanisms, and the challenges faced in achieving universal healthcare access. Thailand excels in inclusivity and financing efficiency, while Indonesia, despite significant progress, still requires improvements in access distribution and medical workforce deployment. This article aims to provide insights into how both countries manage their health insurance systems and offer recommendations to enhance more equitable and sustainable healthcare systems.